Case series of six kidney transplanted patients with COVID‐19 pneumonia treated with tocilizumab. Issue 6 (17th June 2020) - Mella, Alberto; Mingozzi, Silvia; Gallo, Ester; Lavacca, Antonio; Rossetti, Maura; Clari, Roberta; Randone, Olga; Maffei, Stefano; Salomone, Mario; Imperiale, Daniele; Biancone, Luigi
Abstract: Few reports described the outcome of kidney transplanted patients (KTs) affected by COVID‐19 treated with interleukin‐6 receptor inhibitor tocilizumab (TCZ). We report our case series of 6 KTs with COVID‐19 pneumonia who received TCZ: All were of male gender, with a mean age of 55.5 ± 8.4 years, a median time from transplantation of 3611 days (1465‐5757); 5/6 had cardiovascular comorbidities, 1/6 had diabetes, and 3/6 have one or more previous KTs. Four out of six patients died, at an average time of 9.75 ± 2.4 days after tocilizumab administration, 3/6 due to a coexistent septic shock. Two patients improved after TCZ and were discharged at 20 and 21 days, respectively; in both patient, a significant increase of total lymphocyte count was observed. In conclusion, KTs, where the role of peculiar factors such as chronic immunosuppression is still undetermined, represent a high‐risk group with significant COVID‐19‐associated mortality. The evaluation of the TCZ effect in COVID‐19 pneumonia requires controlled studies (ideally RCTs) in this specific population.